Mathematics: A Place of Loving Kindness and Resilience-Building - Cousins, Sarah; Johnston-Wilder, Sue; Baker, Janet Kilpatrick (Journal of the Canadian Association for Curriculum Studies, 2019)
Places of mathematical learning are not always places of loving kindness. Instead, they are sometimes loci of undetected cultural violence (Galtung, 1969) and associated harm. We explore how Cousin’s (2015) interpretation of love in the context of early years relates to building mathematical resilience across the lifespan. Our interpretation of loving kindness in the context of older learners includes unconditional positive regard (Rogers, 1961) and the explicit building of this into the classroom milieu. Education is understood in this work in a broad sense, not only as a means of acquiring knowledge and skills, but also an arena for making connections and gaining a shared understanding about what it is to be human (Tagore, 1933). One of the tools found helpful in the practice of loving kindness, especially where learners have experienced significant prior harm, is the growth zone model (Lugalia, Johnston-Wilder, & Goodall, 2013), informed by the hand model of the brain (Siegel, 2010) and the relaxation response (Benson, 2000). With unconditional positive regard, and with such tools, learners may be empowered to become less avoidant and more engaged with mathematics. They may also acquire resilience, including coping skills, to on greater challenges, once perceived as dangerous. Loving kindness in mathematics is enabling.